Study on the mechanism of mining-induced seismicity triggered by fracture of hard and extremely thick rock stratum: a case study - Jinrong Cao; Linming Dou; Xiufeng Zhang; Siyuan Gong; Yueyong Han; Guoying Li; Chuancheng Liu; Yang Chen (Frontiers in Earth Science)
The control of mining-induced seismicity caused by hard and extremely thick rock stratum (HETRS) has become an important topic in more and more coal mines. This study investigates the mechanisms of mining-induced seismicity through a discrete element numerical model (UDEC-Trigon) calibrated with field data from the Dongtan Coal Mine, China. The failure process of HETRS was categorized into three stages: deformation (Stage I), initial fracture (Stage II), and periodic fracture (Stage III). In the initial fracture stage, the change of vertical displacement is 4.33 m, the change of vertical stress is 26.21 MPa, and the change of seismic energy is 1.91E8 J. The change values during the initial fracture are the largest. A novel method was developed to dynamically track seismic events, identifying tensile failures in central HETRS and shear failures along interfaces. The total decrement of gravitational potential energy is 2.27E10J. The total increment of shear dissipation energy, plastic strain energy and mining-induced seismic energy are 1.16E9J, 1.49E9J and 2.84E10J. Therefore, in addition to elastic energy, gravitational potential energy is also the main source of mining-induced seismic energy and dissipation energy. The mining-induced seismicity energy comes from the fractured strata as well as the surrounding rock. The results provide a unique perspective to understand the mechanism of mining-induced seismicity triggered by HETRS.